Motivation of Self-Growth in the Thought of Imam Ali (peace be upon him) - Abdul Wahid Rahim , Lect . Dr. Arwa (Basra studies journal, 2026)
What Imam ʿAlī (peace be upon him) presented in Nahj al-Balāghah represents a comprehensive system for self-development and motivation. His role was not limited to political or military leadership; rather, it extended to the establishment of an integrated intellectual framework that touches every aspect of human life, offering a firm path for self-growth and the pursuit of perfection. The Imam (peace be upon him) believed that the human being is an ongoing project of development, and that the essence of existence lies in self-awareness. Therefore, motivation in his thought was not confined to moral exhortation, but was deeply connected to personal and social responsibility—where a person becomes an active, constructive force within their family and society in proportion to their ability to reform themselves.